Control of the pulse beetle in stored chickpea and lentil by treating sacks with acetone extract of some selected botanicals (University Journal of Zoology, Rajshahi University, 2007)
Key words: botanicals; sack treatment; Callosobruchus chimensis; lentil; chickpea Univ. j. zool. Rajshahi Univ. Vol.21, 2002. pp. 23-26